2019
DOI: 10.1002/acn3.50878
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Neuroinflammatory–Induced Apoptosis after Traumatic Brain Injury via Nrf2 signaling pathway

Abstract: Objective Dexmedetomidine (DEX) exhibits neuroprotective effects as a multifunctional neuroprotective agent in numerous neurological disorders. However, in traumatic brain injury (TBI), the molecular mechanisms of these neuroprotective effects remain unclear. The present study investigated whether DEX, which has been reported to exert protective effects against TBI, could attenuate neuroinflammatory‐induced apoptosis and clarified the underlying mechanisms. Methods A weight‐drop model was established, and DEX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 28 publications
(29 reference statements)
4
40
0
Order By: Relevance
“…Our in vivo data that the Nrf2-ARE system gets activated in response to TBI (see Fig. 6) This effect could be due to a direct modulatory activity toward Nrf2 expression and activation of the Nrf2-ARE pathway in response to trauma and are in line with the results obtained in a previous study by Li et al indicating significantly enhanced Nrf2, NQO-1 and HO-1 protein expression following TBI (44). However, chronic TS exposure as a stand-alone stimulus has the opposite effect (see Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our in vivo data that the Nrf2-ARE system gets activated in response to TBI (see Fig. 6) This effect could be due to a direct modulatory activity toward Nrf2 expression and activation of the Nrf2-ARE pathway in response to trauma and are in line with the results obtained in a previous study by Li et al indicating significantly enhanced Nrf2, NQO-1 and HO-1 protein expression following TBI (44). However, chronic TS exposure as a stand-alone stimulus has the opposite effect (see Fig.…”
Section: Discussionsupporting
confidence: 92%
“…According to recent studies, while suppression of Nrf2 activity and impairments of the Nrf2-ARE pathway exacerbate TBI-induced oxidative damage as well as post-traumatic neurological deficits, NRF2 played a significant neuroprotective role in TBI and neurodegenerative disorders (4,11). Since the upregulation of Nrf2 activity ameliorates TBI-induced brain injury it could be suggested that positive modulation of Nrf2 could better TBI outcomes through reduction of oxidative stress, inflammation, and protection of BBB integrity (23,24,(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2 is a transcription factor that is associated with Kelch-like ECH-associated protein-1 (Keap1) in the cytosol. During stress or other pathological conditions, Nrf2 dissociates from Keap1 and translocates to the nucleus, where it activates various antioxidant genes and phase II enzymes such as HO-1 and NQO-1 by binding with an ARE, and reduces the oxidative stress and inflammatory response involved in the acute brain injury following a TBI ( Li et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid 2-related factor-2 (Nrf2; also known as Nfe2l2) is a transcription factor and important upregulator of the endogenous cell defense mechanism in response to oxidative damage and is involved in restoration of intracellular homeostasis ( Li et al, 2019b ). Nrf2 is a basic leucine zipper (bZIP) cytoplasmic protein, which translocates into the nucleus under oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study claimed that DEX exerted neuroprotective effect via Nrf2 signaling pathway [17]. The present research utilizes NLRP3 antagonist MCC950, NLRP3 activator Nigericin and Nrf2 inhibitor ML385…”
Section: Introductionmentioning
confidence: 99%